A case of IgG4-related ophthalmic disease after SARS-CoV-2 vaccination: case report and literature review - Zhang, Peixuan; Wu, Qian; Xu, Xiao; Chen, Minliang (Frontiers in Immunology, 2024)
Coronavirus disease 19 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is affecting the world with a surge in cases. A variety of autoimmune diseases occur after SARS-CoV-2 infection or vaccination, of which IgG4-related disease (IgG4-RD) is an important type. IgG4-RD can involve multiple organs of the body. The ocular manifestation of IgG4-RD is called IgG4-related ophthalmic disease (IgG4-ROD). We herein report a patient diagnosed with IgG4-ROD. The patient developed ptosis and vision loss after SARS-CoV-2 vaccination, and the symptoms worsened after SARS-CoV-2 infection. After excluding other diseases like myasthenia gravis and Eaton-Lambert syndrome that may cause ptosis, the diagnosis of IgG4-ROD was confirmed by pathological examination. We discussed the predisposing factors, diagnosis and treatment of this patient to provide a more empirical and theoretical basis for clinical diagnosis and treatment. We conducted a literature review of previously reported cases of IgG4-RD following SARS-CoV-2 infection or vaccination. We retrieved a total of 9 cases, of which 5 developed symptoms after vaccination and 4 after infection. Demographic and clinical characteristics were summarized. In conclusion, our case represents the first case of proven IgG4-ROD after COVID-19 vaccination. We believe that IgG4-ROD and SARS-CoV-2 infection or vaccination are closely related, and the immune system disorder caused by SARS-CoV-2 infection or vaccination may be a key factor in the pathogenesis of IgG4-RD. But for now, there is no direct evidence that there is a causal relationship between SARS-CoV-2 infection or vaccination and IgG4-ROD, which still needs more research and exploration to confirm.